Peningkatan Hasil Belajar Siswa di MTs Negeri 3 Sleman melalui Penggunaan Metode Pembelajaran Card Sort - Arbanginah, Miftakhatul (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
This study aims to identify improvements in learning outcomes of the Quran Hadith through the active sort card learning method in students of grade VIII-C MTs Negeri 3 Sleman Odd Semester of the 2023/2024 academic year. This research is a type of classroom action research through two cycles. The subject of the study was a grade VIII-C student at MTs Negeri 3 Sleman. Data collection techniques in the form of learning outcomes tests taken from giving test questions in each cycle, questionnaire results and interviews with students to provide input on the course of the research process. The results showed that the use of active sort card learning methods can improve the learning outcomes of the Quran Hadith. In pretest cycle 1, the grade point average was 72.50 while at the time of post-test the grade point average was 80.00. While in cycle 2 the average pretest score was 73.50 while the post-test average score was 82.00. The classical completeness criteria also increased by 75% (24 students) in cycle 1 and 93.75% (30 students) in cycle 2.